2023
DOI: 10.1021/acsanm.3c00181
|View full text |Cite
|
Sign up to set email alerts
|

Co/CoO/Lotus Seedpod Nanoporous Carbon Composites Reduced from Co3O4 for High-Performance Microwave Absorbers

Abstract: To obtain microwave-absorbing materials with high absorptivity, broad bandwidth, and lightweight properties, Co 3 O 4 / lotus seedpod carbon (Co 3 O 4 /LSC) composites were reduced under a hydrogen pressure of 3 MPa. As the reduction temperature increases, the phases of the Co 3 O 4 /LSC composites change from Co 3 O 4 to CoO/Co. At 200 °C (named as the 3200 nanocomposite), partial Co 3 O 4 changes to CoO, the Co 3 O 4 completely transfers into CoO with a little Co detectable at 300 °C (3300 nanocomposite), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For this purpose, several high-performing EMA’s have been created in which carbon-based polymer composites are regarded as advantageous and promising candidates for highly efficient EMA with excellent thermal management capacities, lightweight, cost-effective, enhanced electric and heat conductivity, high dielectric loss, high mechanical stability, and excellent corrosion resistance. However, the ability of the carbon nanofillers to agglomerate in the form of bundles results from the presence of powerful intermolecular van der Waals interaction, deteriorates the capabilities of carbon nanofillers for EM absorption, and restricts their applicability in industrial applications. , For this purpose, various techniques have recently been used to construct carbon-decorated hybrid morphologies consisting of magnetic or dielectric particles. For example, Bao et al synthesized the bifunctional hollow Fe@C microsphere and fabricated the nanocomposite microwave absorber by mixing Fe@C (60 wt %) in paraffin, displaying a wide EAB of 7.52 GHz (10.48–18 GHz) at a 1.75 mm thickness . Gou et al made a 2.5 mm thickness nanocomposite consisting of polydimethylsiloxane (PDMS)/CeFe 2 O 4 /graphene oxide (GO) (60 wt %) in paraffin (40 wt %) and achieved the minimum R L value of −52 dB with an EAB of 2.1 GHz (Ku band) .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, several high-performing EMA’s have been created in which carbon-based polymer composites are regarded as advantageous and promising candidates for highly efficient EMA with excellent thermal management capacities, lightweight, cost-effective, enhanced electric and heat conductivity, high dielectric loss, high mechanical stability, and excellent corrosion resistance. However, the ability of the carbon nanofillers to agglomerate in the form of bundles results from the presence of powerful intermolecular van der Waals interaction, deteriorates the capabilities of carbon nanofillers for EM absorption, and restricts their applicability in industrial applications. , For this purpose, various techniques have recently been used to construct carbon-decorated hybrid morphologies consisting of magnetic or dielectric particles. For example, Bao et al synthesized the bifunctional hollow Fe@C microsphere and fabricated the nanocomposite microwave absorber by mixing Fe@C (60 wt %) in paraffin, displaying a wide EAB of 7.52 GHz (10.48–18 GHz) at a 1.75 mm thickness . Gou et al made a 2.5 mm thickness nanocomposite consisting of polydimethylsiloxane (PDMS)/CeFe 2 O 4 /graphene oxide (GO) (60 wt %) in paraffin (40 wt %) and achieved the minimum R L value of −52 dB with an EAB of 2.1 GHz (Ku band) .…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [20] synthesized Co-nanoparticle-loaded carbon nanosheets via a simple swelling and carbonization treatment of cellulose fibrils, and confirmed that the anisotropy derived from the lamellar structure of two-dimensional carbon materials was responsible for the magnetic resonance. Qi et al [21] prepared a composite of Co/CoO/LSC (lotus seedpod carbon) with the carbonization of lotus seedpods and hydrogen reduction of Co 3 O 4 , in which the 3D porous biomass-derived carbon was proven to be conducive to microwave absorption for the improvement of impedance match and multiple scattering. All of the above works are based on the composites of 0D magnetic metals (or their alloys and oxides) and 0-3D carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [20] synthesized Co nanoparticles loaded carbon nanosheets via a simple swelling and carbonization treatment of cellulose fibril and confirmed that the anisotropy derived from the lamellar structure of two-dimensional carbon materials was responsible for magnetic resonance. Qi et al [21] prepared the composite of Co/CoO/LSC (lotus seedpod carbon) by carbonization of lotus seedpods and hydrogen reduction of Co3O4, in which the 3D porous biomass-derived carbon was proved to be conducive to microwave absorption for the improvement of impedance match and multiple scattering. All of the above works are based on the composites of 0D magnetic metals (or their alloys and oxides) and 0-3D carbon materials.…”
Section: Introductionmentioning
confidence: 99%